Multiseason recoveries of organic and inorganic nitrogen-15 in tropical cropping systems - Dourado Neto, Durval; Powlson, David S.; Abu Bakar, Mohd Rizam; Bacchi, Osny Oliveira Santos; Basanta, Maria del Valle; Cong, Phan Thi; Keerthisingh, Gamini; Ismaili, Mohammed; Rahman, Mohammad Saidur; Reichardt, Klaus; Safwat, Mohamed Said Ali; Sangakkara, Ravi; et al. (2009)
In tropical agroecosystems, limited N availability remains a major impediment to increasing yield. A 15N-recovery experiment was conducted in 13 diverse tropical agroecosystems. The objectives were to determine the total recovery of one single 15N application of inorganic or organic N during three to six growing seasons and to establish whether the losses of N are governed by universal principles. Between 7 and 58% (average of 21%) of crop N uptake duringthe first growing season was derived from fertilizer. On average, 79% of crop N was derived from the soil. When 15N-labeled residues were applied, in the first growing season 4% of crop N was derived from the residues. Average recoveries of 15N- labeled fertilizer and residue in crops after the first growing season were 33 and 7%, respectively. Corresponding recoveries in the soil were 38 and 71 %. An additional 6% of the fertilizer and 9.1 % of the residue was recovered by crops during subsequent growing seasons. There were no significant differences in total 15N recovery (average 54%) between N from fertilizer and N from residue. After five growing seasons, more residue N (40%) than fertilizer N (18%) was recovered in the soil, better sustaining the soil organic matter N content. Long-term total recoveries of 15N-labeled fertilizer or residue in the crop and soil were similar. Soil N remained the primary source of N for crops. As higher rainfall and temperature tend to cause higher N losses, management practices to improve N use efficiency and reduce losses in wet tropical regions will remain a challenge.